2022
DOI: 10.3390/f13122015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forest Gap on Soil Microbial Communities in an Evergreen Broad-Leaved Secondary Forest

Abstract: Forest gaps play a crucial role in community succession and assembly in forest ecosystems; therefore, they have recently been recognized and implemented as effective forest management practice all over the world. Forest gaps are commonly created as small disturbances in secondary forests to improve forest regeneration, nutrient cycling, ecosystem functioning, and biodiversity. The objective of this study was to investigate the responses of the physico-chemical and biological properties and microbial communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This came after the fire in 2005, which created specific conditions for this site. Previously, for evergreen broad-leaf forests in China, it was found that forest gaps may decrease soil microbial community diversity, soil nutrients, and, as a consequence, the heterotrophic part of soil emission [42].…”
Section: Soil Emission and Times Since Firementioning
confidence: 99%
“…This came after the fire in 2005, which created specific conditions for this site. Previously, for evergreen broad-leaf forests in China, it was found that forest gaps may decrease soil microbial community diversity, soil nutrients, and, as a consequence, the heterotrophic part of soil emission [42].…”
Section: Soil Emission and Times Since Firementioning
confidence: 99%